Comprehensive evaluation model of wind farm site selection based on ideal matter element and grey clustering. (1st November 2020) - Tan, Qingkun; Wei, Tang; Peng, Wu; Yu, Zhang; Wu, Chenrui
Abstract: China has carried out the relevant research on the evaluation of the wind farm site selection, but the evaluation index are mainly from the economic aspect and comprehensive benefit evaluation research of the wind farm site selection exists defects. In order to comprehensively to consider the explicit and implicit benefits of wind farms, firstly, a comprehensive evaluation index system for the wind farm site selection is established, which mainly includes economic, environmental and social aspects. Secondly, an integrated weight model with subjective and objective weight method is constructed, and the ideal matter element extension evaluation model and the grey clustering evaluation model for the wind farms site selection are proposed. Finally, case studies show that the proposed comprehensive evaluation model can rank the comprehensive benefits of wind farms site selection. Based on the comprehensive evaluation results of wind farm site selection, a comprehensive evaluation model of wind farm site selection is proposed to this paper, which can provide the decision basis of the decision makers. This paper establishes an index evaluation model from three aspects of economy, environment and society, examines the advantages and disadvantages of each access location of wind power system, so as to make a reasonable site selection. In view of the current development of the electricity market, this paper constructs a differential weighting model based on the built evaluation model for wind power system location. The simulation results show that the proposed model can effectively guide the location optimization of wind power system. Highlights: A comprehensive evaluation index system for the wind farm site selection is established. An integrated weight model with subjective and objective weight method is constructed. The ideal matter element extension evaluation model and the grey clustering evaluation model.